THE FORGOTTEN LIONESS: RASIMAH ISMAIL, MINANGKABAU WOMAN AGAINST DUTCH COLONIALISM IN WEST SUMATRA - Hutagalung, Albertus; Nopriyasman, Nopriyasman; Asnan, Gusti (Marwah: Jurnal Perempuan, Agama dan Jender, 2024)
This article discusses the role of Rasimah Ismail in resisting Dutch colonialism in West Sumatra between 1912 and 1933. Its background includes the historical context of Dutch colonialism in Indonesia and the political and social situation in West Sumatra during that period. The aim of this research was to understand the role and contribution of Rasimah Ismail in the resistance against Dutch colonization. The research method used included historical analysis based on primary and secondary sources consisting of several stages: heuristic, criticism, interpretation, historiography. Sources sought included archives, photographs, as well as Dutch and Indonesian newspapers conducted online and offline. The findings highlighted Rasimah Ismail's important role in organizing Minangkabau women to resist Dutch colonialism through various social and political activities and actively demanding Indonesian independence. Rasimah Ismail was also known for her bravery and firmness in expressing opinions against colonial government policies, leading to her exile and imprisonment in Semarang. The conclusion of this article emphasized the importance of women's roles in anti-colonial resistance movements and paid tribute to Rasimah Ismail as one of the active figures in that struggle.